Antibacterial Potential of Marine Brown Algae Turbinaria Conoides Against Bacteria Associated with Diabetic Foot Ulcer: Life Sciences-Botany - Chitrikha Suresh, T.; Poonguzhali, T. V.; Anuradha, V.; Bharathi, S.; Ramesh, B.; Suresh, G. (International Journal of Life Science and Pharma Research, 2023)
The marine brown algae Turbinaria conoides was extracted with different solvents, viz., acetone, ethanol, methanol and distilled water. The extracts were screened for the presence of various phytochemicals and examined for antibacterial activity by agar well diffusion method. Diabetic foot ulcer (DFU) associated bacteria and their respective standard strains, such as Staphylococcus aureus ATCC 5923, Pseudomonas aeruginosa ATCC 27853, Klebsiella pneumoniae ATCC 700603 and Enterococcus faecal ATCC 25922 were used as test bacteria. Among the different solvent extracts, the aqueous extract possessed the maximum zone of inhibition against both test and standard bacterial strains. The minimal inhibitory concentration (MIC) and minimal bactericidal concentration (MBC) of the aqueous extract against test pathogens were 128-4μg. The eluent mixture for separating the active fraction was selected by thin layer chromatography (TLC), which was found to be n-hexane: ethylacetate (6:4) with a maximum of four spots. In column chromatography, 25th -27th-minute fractions showed maximum antibacterial activity against all the DFU bacterial strains. Our study aims to find the use of T. conoides for treating DFU-associated bacterial infections. The objectives include exploring different solvent extracts of T. conoides for antibacterial activity and characterization of bioactive metabolite.